Improving reading comprehension skill through Listen-Read-Discuss (LRD) learning strategy - Nur Faindah Syamsir; Zul Astri; Suhartina Suhartina; Fhadli Noer (Journal of Science and Education (JSE), 2021)
The problem in this research is the students' reading comprehension skills in English. The purpose of this study to investigate the improvement in reading comprehension skills of VIII grade students of SMP Negeri 5 Manda in Maros Regency. This type of research is experimental research. The technique of collecting data is done by using a test technique. The test instrument is in the form of multiple-choice questions tested before and after being treated with learning strategies. The data analysis technique used the t-test. Based on the calculation of the difference test, the average value of the data in the t-test for the equations of means column has a significance value of 0.025> 0.000, so H0 is rejected, so it can be concluded that the Listening-Read-Discuss (LRD) Learning Strategy can be used to improve reading comprehension skills in students.